Development of Nucleic‐Acid‐Based Electrochemical Biosensors for Clinical Applications. (27th October 2022) - Zhang, Zijie; Sen, Payel; Adhikari, Bal Ram; Li, Yingfu; Soleymani, Leyla
Abstract: Nucleic acids are remarkable molecules. In addition to Watson–Crick base pairing, the different structural motifs of these molecules can bind non‐nucleic acid targets or catalyze chemical reactions. Additionally, nucleic acids are easily modified with different molecules or functional groups. These properties make nucleic acids, particularly DNA, ideally suited for use in electrochemical biosensors, both as biorecognition elements and redox reporter probes. In this Minireview, we will review the historical evolution of nucleic acids as probes in electrochemical biosensors. We will then review the specific examples of nucleic‐acid‐based biosensors that have been evaluated for clinical use in the areas of infectious disease, cancer, or cardiovascular health. Abstract : This Minireview discusses the role of nucleic acids as biorecognition and/or reporter probes in electrochemical biosensors. It highlights specific examples of nucleic‐acid‐based electrochemical sensors that have been evaluated with clinical or clinically relevant samples for the management of infectious disease, cancer, or cardiovascular health.